EFFICIENCY OF PINEAPPLE MARKETING CHANNELS IN SABULAKOA SUB-DISTRICT, SOUTH KONAWE DISTRICT - Gede Suardana Putra; Abdi, Abdi; Hadi Sudarmo (International Journal of Technology and Education Research, 2024)
Indonesia faces stiff competition in the era of global economy and free trade of horticultural products, especially fruits, where high quality and continuous availability are key. As the third largest pineapple producing country in the world, a supply chain approach is essential to understand the marketing aspects and ensure the efficiency of pineapple distribution, especially in Sabulakoa District, South Konawe, which has great local economic potential but is faced with the challenge of an inefficient supply chain, affecting prices and farmers' profits. This study aims to (1) determine the marketing channel, and (2) determine the magnitude of marketing efficiency in pineapple commodities in Sabulakoa District. This research is a qualitative and quantitative research with a population of 50 pineapple farmers and a sample of 33 people taken using simple random sampling technique through the Slovin formula. Research procedures were carried out by observation, interviews, and literature study, and data analysis using marketing margin analysis techniques and marketing efficiency. Based on the results of the study, pineapple marketing channels in Sabulakoa Subdistrict consist of channel I: pineapple farmers - retailers - consumers, channel II: pineapple farmers - intermediary traders - consumers, and channel III: pineapple farmers - intermediary traders - retailers - consumers. The efficiency value of marketing channel I is 71.43%, marketing channel II is 55.56%, and marketing channel III is 50%